ANALISIS PENGENDALIAN KOROSI PADA PERMUKAAN BASAH KAPAL-KAPAL BAJA DENGAN MENGGUNAKAN ZINK ANODA - Sonja T. A. Lekatompessy (ALE Proceeding, 2021)
Zink anodes are very importantfor reducing the corrosion rate on underwater surface area of hull plates. Zink anodes are affixed to parts of the vessel that are prone to seawater corrosion. This study aims to find out how much influence the installed current has on the corrosion rate by analyzing the data on the use of zink anodes in the field and the data on the use of zink anodes as a result of calculations so that the use of strong currents installed according to the need will reduce the rate of corrosion. To see the strong influence of current on the rate of corrosion, it takes data on the corrosion rate of the last 5 years from 9 vessels and also the number of zink anodes used each year. From the graph of the results of the calculation of strong current according to the theory and the results of the use of zinc anodes on nine vessels, the results obtained it is clear that the installed current strength must meet the needs of each vessel because it will affect the decrease in corrosion rate. On vessel No.3, an excess current strength of 0.539Amp to 1,386 Amp, a decrease in corrosion rate reaching 0.0317 mm/year in the 5th year. On vessel No. 4, an excess current strength of 0.444 Amp to 1.822 Amp there is a decrease in corrosion rate reaching 0.0138 mm/year in the 5th year. On vessel No. 9, an excess strong current of 4,894 Amp to 5,793 Amp there is a decrease in corrosion rate reaching 0.0371 mm/year in the 5th year.